Differential knockdown of TGF-β ligands in a three-dimensional co-culture tumor- stromal interaction model of lung cancer - Horie, Masafumi (BioMed Central, 2014)
BACKGROUND: Transforming growth factor (TGF)-β plays a pivotal role in cancer progression through regulating cancer cell proliferation, invasion, and remodeling of the tumor microenvironment. Cancer-associated fibroblasts (CAFs) are the predominant type of stromal cell, in which TGF-β signaling is activated. Among the strategies for TGF-β signaling inhibition, RNA interference (RNAi) targeting of TGF-β ligands is emerging as a promising tool. Although preclinical studies support the efficacy of this therapeutic strategy, its effect on the tumor microenvironment in vivo remains unknown. In addition, differential effects due to knockdown of various TGF-β ligand isoforms have not been examined. Therefore, an experimental model that recapitulates tumor–stromal interaction is required for validation of therapeutic agents. METHODS: We have previously established a three-dimensional co-culture model of lung cancer, and demonstrated the functional role of co-cultured fibroblasts in enhancing cancer cell invasion and differentiation. Here, we employed this model to examine how knockdown of TGF-β ligands affects the behavior of different cell types. We developed lentivirus vectors carrying artificial microRNAs against human TGF-β1 and TGF-β2, and tested their effects in lung cancer cells and fibroblasts. RESULTS: Lentiviral vectors potently and selectively suppressed the expression of TGF-β ligands, and showed anti-proliferative effects on these cells. Furthermore, knockdown of TGF-β ligands attenuated fibroblast-mediated collagen gel contraction, and diminished lung cancer cell invasion in three-dimensional co-culture. We also observed differential effects by targeting different TGF-β isoforms in lung cancer cells and fibroblasts. CONCLUSIONS: Our findings support the notion that RNAi-mediated targeting of TGF-β ligands may be beneficial for lung cancer treatment via its action on both cancer and stromal cells. This study further demonstrates the usefulness of this three-dimensional co-culture model to examine the effect of therapeutic agents on tumor–stromal interaction. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1471-2407-14-580) contains supplementary material, which is available to authorized users.